London's Marginal Histories - Rogers, Nicholas (Labour / Le Travail, 2007)
The article reviews and comments on several books including "Violent London: 200 Years of Riots, Rebels an Revolts," by Clive Bloom, "Down and Out in 18th-Century London," by Tim Hitchcock, and "The London Mob: Violence and Disorder in 18th-Century England," by Robert Shoemaker.
Keywords: BLOOM, Clive; BOOKS -- Reviews; DOWN & out in 18th Century London (Book); HITCHCOCK, Tim; LONDON Mob: Violence & Disorder in 18th Century England, The (Book); Nonfiction; SHOEMAKER, Robert; VIOLENT London: 2000 Years of Riot, Rebels & Revolts (Book)

Liberty or Death. Early Struggles for Parliamentary Democracy - Rogers, Nicholas (Labour / Le Travail, 2004)
The article reviews the book, "Liberty or Death. Early Struggles for Parliamentary Democracy," by Ray Hemmings.

Filming Peterloo in the Age of Brexit - Rogers, Nicholas (Labour / Le Travail, 2019)
The article reviews the film, "Peterloo," directed by Mike Leigh.

Dissenting Traditions: Essays on Bryan D. Palmer, Marxism, and History - Carleton, Sean; McCoy, Ted; Smith, Julia; Finkel, Alvin; Niergarth, Kirk; Kealey, Gregory S.; Rogers, Nicholas; Pearson, Chad; Panitch, Leo; Gindin, Sam; McIlroy, John; Campbell, Alan; et al. (Working Canadians: Books from the CCLH, 2021)
The work of Bryan D. Palmer, one of North America’s leading historians, has influenced the fields of labour history, social history, discourse analysis, communist history, and Canadian history, as well as the theoretical frameworks surrounding them. Palmer’s work reveals a life dedicated to dissent and the difficult task of imagining alternatives by understanding the past in all of its contradictions, victories, and failures. Dissenting Traditions gathers Palmer’s contemporaries, students, and sometimes critics to examine and expand on the topics and themes that have defined Palmer’s career, from labour history to Marxism and communist politics. Paying attention to Palmer’s participation in key debates, contributors demonstrate that class analysis, labour history, building institutions, and engaging the public are vital for social change. In this moment of increasing precarity and growing class inequality, Palmer’s politically engaged scholarship offers a useful roadmap for scholars and activists alike and underlines the importance of working-class history. --Publisher's description